2022
DOI: 10.12659/msm.937331
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Year Clinical Evaluation of Endodontically Treated Posterior Teeth Restored with Resin Nanoceramic Computer-Aided Design/Computer-Aided Manufacture (CAD/CAM)-Fabricated Partial Crowns

Abstract: Background We aimed to investigate the clinical effects of resin nanoceramic (RNC) computer-aided design/computer-aided manufacture (CAD/CAM) partial crowns on posterior teeth after root canal treatment over a 3-year period. Material/Methods A total of 132 posterior teeth restored with CAD/CAM partial crowns were placed in 128 patients. The observation group (n=66) was restored with RNC restorations, while the control group received lithium disilicate-based glass cerami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, obtaining strong and stable resin bonds to CCRBCs poses a challenge 4 . Clinical studies have demonstrated favorable outcomes for restorations made from CCRBCs, but there is some evidence indicating a higher rate of debonding failure rate compared with glass ceramic restorations 5,6 . This underscores the need for further research aimed at enhancing CCRBC adhesion to improve the durability and lifespan of such restorations.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining strong and stable resin bonds to CCRBCs poses a challenge 4 . Clinical studies have demonstrated favorable outcomes for restorations made from CCRBCs, but there is some evidence indicating a higher rate of debonding failure rate compared with glass ceramic restorations 5,6 . This underscores the need for further research aimed at enhancing CCRBC adhesion to improve the durability and lifespan of such restorations.…”
Section: Introductionmentioning
confidence: 99%